Biodiesel Production from Used Cooking Oil over Nickel-modified Calcium Phosphate Scum (Ni-CaPs) Catalyst from the Sugar Refining Industry - O. U. Osazuwa; D. O. Nekekpemi (Journal of Applied Sciences and Environmental Management)
The increasing global energy demand has sparked a search for sustainable fuel sources. Biodiesel from organic waste offers a promising solution to reduce carbon emissions. Hence, the objective of this paper was to synthesize biodiesel production from used cooking oil using nickel-modified calcium phosphate scum (Ni-CaPs) from sugar refining industry as a catalyst. X ray diffraction analysis revealed the crystalline structure of CaO, NiO, and SiO2. X-ray fluorescence showed a composition of 50.316 % CaO, 4.61 % NiO, and 18.60 % SiO2. Fourier Transform Infrared spectroscopy identified functional groups associated with C-N, C-Cl, and C-H stretching bonds. Scanning Electron Microscopy and Energy Dispersive X-ray analysis confirmed the catalyst's morphological and compositional properties. Response Surface Methodology (RSM) optimized the reaction conditions: 55°C, 90 mins, 1 wt. % catalyst loading, and 12:1 methanol-to oil molar ratio. This yielded 93.2 % biodiesel, with an R2 value of 0.9886. The Ni-CaPs catalyst offers cost-effectiveness, simple synthesis process, stability, and widespread availability of raw materials. This study demonstrates the potential of Ni-CaPs as a sustainable, efficient catalyst for biodiesel production from waste materials, contributing to a more environmentally friendly energy solution.